Physical and Rheological Properties of Poly-floral Honey from the Iraqi Kurdistan Region and the Effect of Temperature on its Viscosity - Azawy, Auday K.; Ibrahim, Kocher J.; Abdullah, Omed Gh.; Othman, Beshroo A.; Al-Saadi, Jasim M.S. (Current Nutrition & Food Science, 2021)
Aims: In this study, the physical and rheological properties of three poly-floral honey samples collected from different places in the Kurdistan region were determined. Methods: The honey samples were analyzed for pH, free acidity, total ash content, moisture content, refractive index, soluble solids (Brix), electrical conductivity, volume expansion, density, specific heat capacity, surface tension, and rheological properties. The pH and free acidity of the honey samples varied from 4.10 to 4.81 to 30 to 62 mEq/kg, respectively. The total ash content ranged from 0.166 to 0.408%. The moisture content, soluble solids, and refractive index ranged from 15.60 to 16.60 g/100 g, 83.40 to 84.40, and 1.4998 to 1.5023, respectively. The electrical conductivity ranged from 40.896 to 44.471 mS/cm. The linear relationship between the electrical conductivity and the ash content was also calculated in this investigation. The volumetric expansion coefficient of the honey samples varied from 6.0098x10-4 to 6.69942x10-4 mm3/K. The density ranged from 1.42125995 to 1.45501137 g/cm3. The specific heat capacity varied from 2448.078 to 2575.004 J/kg.K. The surface tension varied from 0.2178 to 0.2282 N/m. The apparent viscosity was measured by Brookfield Viscometer, and the dynamic viscosity was measured by HAAKE Falling Ball Viscometer, after changing the temperature from 293 to 323 K. Results and Discussion: The honey samples of lower moisture content showed a greater increase in their apparent and dynamic viscosities. Arrhenius model was used to describe the effect of temperature on the honey viscosity. This model was used to determine the activation energy. Other rheological properties such as kinematic viscosity and fluidity, were also determined. Conclusion: All the honey samples behaved as Newtonian fluids in the whole temperature range.
Keywords: specific heat capacity